Birthright (2014), volume 7 ebook Blood brothers. - Joshua, Williamson (Birthright (2014), 2019)
As the search for Brennan and Kallista begins, Mikey still has much to atone for. In the wake of the previous volume's events, can he become Earth's greatest protector, or have his actions already doomed his new quest? Collects BIRTHRIGHT #31-35. Author: Joshua Williamson. Illustrator: Andrei Bressan, Adriano Lucas . 2019 Skybound LLC.